Effect of storage duration on the color value of sweet potatoes (Ipomoea batatas) - Shaari, Nurfarhana; Shamsudin, Rosnah; Mohd Nor, Mohd Zuhair; Hashim, Norhashila; Hamzah, Azman (Malaysian Society of Agricultural Engineers, 2019)
Sweet potato (Ipomoea batatas) is a cultivar belongs to the family of Convolvulaceae, a herbacous and woody species. This cultivar is recommended as a superior source for the production of foods with health benefits. The quality of sweet potatoes must be maintained especially during postharvest storage to ensure its health benefits not affected. Colour is an important parameter which reflects the quality of sweet potato in terms of appearance and nutrients. Therefore, the effect of storage duration on the colour of sweet potato after exposure for ten days at room temperature were investigated. The colour parameters in terms of L-,a-,b-values, Hue and Chroma were determined using colour reader (CR-10,Conica Minolta, Japan). A significant (p < 0.05) decreased about 8% and 28.64% was observed in L-values and a-values respectively after 10 days of storage. The b-values and hue increased significantly (p < 0.05) by 26.49% and 43.28% respectively. However, the chroma value shows no significant different during the storage. Therefore, this finding indicates that storage time significantly effects the color value of sweet potatoes. This knowledge will offer potential application in sweet potatoes industry especially in developing a system to maintain the freshness and quality of sweet potatoes during the storage.